Neurodivergence and violent extremism: aggregate data for 18 international case studies, 2023 - Salman, Nadine (UK Data Service, 2023)
This research adopted a case study analysis approach, analysing a novel dataset of 18 closed-source international cases of individuals with extremism concerns who were diagnosed with, or undergoing diagnosis for, autism. This file provides a summary of the data relating to specific variables collected as part of this research. The variables presented here include additional metadata about the cases, primarily comprising categorical variables used to summarise the cases. The remaining data was obtained through qualitative case study summaries which were aggregated and summarised in the research paper. This qualitative data is not included in this document due to the sensitivity and potentially identifiable information provided in the case study summaries. This document contains two sheets: 1. Variables Collected This sheet summarises the variables collected, the type of data collected for each of these variables, and the categorical options for categorical variables that were coded at the point of data entry. 2. Data Summary This sheet presents a summary of the data collected across all the cases. Due to the sensitivity and personal information contained in the original dataset, the data are presented in tables which are aggregated across cases. This is to ensure that no single case is identifiable from the data. This is one of the projects managed under the Centre for Research and Evidence on Security Threats (CREST). This project aims to consolidate best practice in assessing the risk of extremism in individuals. Specifically, this project examines neurodivergence in the context of extremism vulnerability, risk, resilience, and opportunities for risk management.